Analisis Deskripsi Profesi Guru - Meisie L. Mangantes; Tellma Tiwa; Gorius Geor; Virginia A. Tuwaidan (Departement of Mathematics Education, 2024)
This study is a qualitative research approach that is Library Research is a study that obtained all the data from various library literature in the form of books, articles and other works. In this case to know scientifically about the analysis of the description of the teacher profession the nature and duties of teachers and the purpose of a strong understanding of teachers so that the educational process can run properly. Data collection technique is done through direct citation technique and indirect citation technique. Data analysis was performed using content analysis techniques. An attempt to objectively and systematically describe and deeply analyze the content of written or printed information. Therefore, the results of this study give the conclusion that the teacher is a very important profession in the world of Education. The factors that affect the professionalism of teachers include the standard qualifications of teachers, the interrelation of teacher disciplines, pedagogical, professional, social and personal competencies, as well as the development of student potential. In addition, the duties and responsibilities of teachers in teaching and learning activities include mastering teaching materials, facilitating the teaching and learning process, creating a conducive learning atmosphere, and planning and implementing the learning process. Therefore, teachers who have the appropriate academic ability need to continue to improve their qualifications and abilities to become professional and qualified teachers. The development of teacher professionalism can also be achieved through Career Development and proper training. To solve problems. With the relationship between teacher professionalism in the learning process with student learning outcomes. More professional teachers tend to have a more positive impact on student learning outcomes.